Synthesis and Structural Studies on Mn(II) Complexes with Some β-Ketoimines. - K. AGARWAL , S.; KUMAR , MUKESH; Chand, Subhash (Asian Journal of Chemistry, 2010)
Mn(II) complexes having the formulae Mn(L)2, where L ═ 4-p-dimethyl amino-anilino-3-penten-2-one, 4-(β-mercapto) ethyl amino-3-penten-2-one, 4-(4-phenyl thiazole-2) amino-3-penten-2-one, 4-(2-hydroxy-penten)- 3-pyridyl ketoimine and O-(4-imino-3-penten-2-one) benzene sulphonic acid have been prepared. The complexes show non-electrolytic behaviour. All the complexes have either octahedral or high spin tetrahedral geometries.